STUDY ON THE GERMINATION OF OOSPORES OF P. PALM1VORA - R. K. HEGDE, P. SANTHA KUMARP AND (Indian Phytopathology, 2002)
Oospores of P. palmiuora (But.) Butler were germinated using different techniques. A common garden snail observed in the are cal pepper plantations of Karnataka was Cryptozona semirugata Beck. Fifty five per cent germination of oospores of P. palmiuora were recorded after ingestion by the snail. Maximum germination of oospores (83.33 per cent) was obtained when ,B-glucuronidase was at 10 ppm at 14 h.